Longterm Survival After Liver Transplantation for Autoimmune Hepatitis: Results From the European Liver Transplant Registry. Issue 7 (1st May 2020) - Heinemann, Melina; Adam, Rene; Berenguer, Marina; Mirza, Darius; Malek‐Hosseini, Seyed Ali; O'Grady, John G.; Lodge, Peter; Pratschke, Johann; Boudjema, Karim; Paul, Andreas; Zieniewicz, Krzysztof; Fronek, Jiri; et al.
Abstract : The aim of this study was to analyze longterm patient and graft survival after liver transplantation for autoimmune hepatitis (AIH‐LT) from the prospective multicenter European Liver Transplant Registry. Patient and liver graft survival between 1998 and 2017 were analyzed. Patients after AIH‐LT (n = 2515) were compared with patients receiving LT for primary biliary cholangitis (PBC‐LT; n = 3733), primary sclerosing cholangitis (PSC‐LT; n = 5155), and alcohol‐related cirrhosis (AC‐LT; n = 19, 567). After AIH‐LT, patient survival was 79.4%, 70.8%, and 60.3% and graft survival was 73.2%, 63.4%, and 50.9% after 5, 10, and 15 years of follow‐up. Overall patient survival was similar to patients after AC‐LT ( P  = 0.44), but worse than after PBC‐LT (hazard ratio [HR],  1.48; P  < 0.001) and PSC‐LT (HR,  1.19; P  = 0.002). AIH‐LT patients were at increased risk for death (HR,  1.37‐1.84; P  < 0.001) and graft loss (HR,  1.35‐1.80; P  < 0.001) from infections compared with all other groups and had a particularly increased risk for lethal fungal infections (HR,  3.38‐4.20; P  ≤ 0.004). Excluding patients who died within 90 days after LT, risk of death after AIH‐LT was superior compared with AC‐LT (HR,  0.84; P  = 0.004), worse compared with PBC‐LT (HR,  1.38; P  < 0.001) and similar compared with PSC‐LT ( P  = 0.93). Autoimmune hepatitis (AIH) patients with living donor liver transplantation (LDLT) showed reduced survival compared with patients receiving donation after brain death (HR,  1.96; P  < 0.001). In AIH‐LT patients, overall survival is inferior to PBC‐LT and PSC‐LT. The high risk of death after AIH‐LT is caused mainly by early fatal infections, including fungal infections. Patients with LDLT for AIH show reduced survival.